2021
DOI: 10.1111/cyt.13056
|View full text |Cite
|
Sign up to set email alerts
|

Can cytology reliably subtype non‐small cell lung carcinomas?

Abstract: Organization classification of lung tumours, recommends the subtyping of non-small cell lung carcinomas (NSCLC) into squamous cell carcinoma (SQC) and adenocarcinoma (ADC) histology. [1][2][3] In other words, emphasis is put on differentiating NSCLC into ADC and SQC in cytology as well as small biopsy specimens as a standard of care for accurate targeted therapy of these patients. It is therefore not sufficient to separate small cell lung carcinoma (SCLC) from NSCLC; further distinction of NSCLC is warranted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The strength of agreement between the findings of bronchial brushing and bronchial biopsy was found to be moderate in this study. This result is in accordance with the studies by Patel et al and Jain et al, which showed fair-to-high concordance between these modalities in subtyping NSCLC [2,8].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The strength of agreement between the findings of bronchial brushing and bronchial biopsy was found to be moderate in this study. This result is in accordance with the studies by Patel et al and Jain et al, which showed fair-to-high concordance between these modalities in subtyping NSCLC [2,8].…”
Section: Discussionsupporting
confidence: 93%
“…Herein, 30-50% of NSCLCs were not classified further and were designated by the term NSCLC-not otherwise specified (NSCLC-NOS) [3,7]. With the identification of molecular differences and the emergence of target therapy for different subtypes of NSCLC differentiating squamous cell carcinoma (SCC) from adenocarcinoma (ADC) has become necessary [3,5,7,8]. Prediction of the improved response of epidermal growth factor receptor (EGFR)-positive ADC to tyrosine kinase inhibitor and pemetrexed and potential toxicity of bevacizumab in SCC emphasize the need for this differentiation [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A thorough appraisal of the possibilities offered by cytology in this area is provided by Jain & Bubendorf. 1 Cytopathology approaches, when used in conjunction with immunohistochemistry, can provide accurate and speedy diagnosis and classification of lung cancers, enabling patient management.…”
Section: Editorialmentioning
confidence: 99%
“…Small cell carcinomas are managed differently to pulmonary squamous and adenocarcinomas in the advanced disease setting, and a small cell carcinoma diagnostic label may be all that is required currently for appropriate management decisions to be made, although this may change in the near future. A thorough appraisal of the possibilities offered by cytology in this area is provided by Jain & Bubendorf 1 . Cytopathology approaches, when used in conjunction with immunohistochemistry, can provide accurate and speedy diagnosis and classification of lung cancers, enabling patient management.…”
mentioning
confidence: 99%